Bright vortex solitons in bose condensates - Adhikari, S. K. [UNESP] (Springer Nature, 2004)
We suggest the possibility of observing and studying bright vortex solitons in attractive Bose-Einstein condensates in three dimensions with a radial trap. Such systems lie on the verge of critical stability and we discuss the conditions of their stability. We study the interaction between two such solitons. Unlike the text-book solitons in one dimension, the interaction between two radially trapped and axially free three-dimensional solitons is inelastic in nature and involves exchange of particles and deformation in shape. The interaction remains repulsive for all phase δ between them except for δ ≈ 0.